STUDYING THE NATURE OF EXOTIC BLACK HOLES - M. Melibaev (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract:  Considered  theoretical  model  of  creation  Black  Holes  as  solution Schwarzschild  metric  of  Einstein's  equation.  As  considered  as  final  achievements hunger and binary Black Holes Systems which accretion leading to perturbation of space-time metric structure and create gravitational waves.